The influence of the leader in the formation of a high-performance team: A literature review - Marinho, Matheus Monteiro Gonçalves; Moura, Maria Lucia Costa de; Kontoyannopoulos, Rebeca de Mendonça (Seven Editora, 2024)
The objective was to know the main theoretical concepts about high performance teams and to analyze the role of the leader as a builder and performance evaluator. It is based on the bibliographic method, it will show that, although the relevance of the leader is indisputable, there is no one leadership model that is so much more efficient than another, but rather, that the effectiveness of the leader's style depends on the stimulus used, the situation presented, with which team profiles and in which environment. Due to business competitiveness, the formation of high-performance teams and a leader capable of developing it gains prominence on the global scene, in this way, it is essential to understand the advantages that these teams can provide to the organization, the leader and team are essential to increase productivity, however, it is necessary that its members are committed to the goals,  have a synergistic relationship and jointly apply their skills. DOI:https://doi.org/10.56238/sevened2024.010-061